2021
DOI: 10.1083/jcb.201911114
|View full text |Cite
|
Sign up to set email alerts
|

Completion of neuronal remodeling prompts myelination along developing motor axon branches

Abstract: Neuronal remodeling and myelination are two fundamental processes during neurodevelopment. How they influence each other remains largely unknown, even though their coordinated execution is critical for circuit function and often disrupted in neuropsychiatric disorders. It is unclear whether myelination stabilizes axon branches during remodeling or whether ongoing remodeling delays myelination. By modulating synaptic transmission, cytoskeletal dynamics, and axonal transport in mouse motor axons, we show that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 121 publications
(238 reference statements)
0
22
0
Order By: Relevance
“…Taken together, the experiments performed by Wang et al (2) suggest that as multiple axons actively compete for synaptic dominance at the NMJ, the myelination of their terminal branches is delayed. Upon synapse elimination, neuromuscular activity promotes a retrograde signal that increases maturity of the microtubule cytoskeleton.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Taken together, the experiments performed by Wang et al (2) suggest that as multiple axons actively compete for synaptic dominance at the NMJ, the myelination of their terminal branches is delayed. Upon synapse elimination, neuromuscular activity promotes a retrograde signal that increases maturity of the microtubule cytoskeleton.…”
mentioning
confidence: 74%
“…These two axons then further compete for synaptic territory, leaving one "winner" that eventually occupies the motor endplate by the end of the second postnatal week. To determine the relationship between synapse elimination and myelination, Wang et al (2) used the formation of paranodal junctions between axons and Schwann cells as a surrogate for myelination and then determined whether axons that occupied NMJs in a singly or dually innervated state were more or less likely to be myelinated. They found that when the NMJ is dually innervated, myelination of the terminal axon branch is inhibited; neither synaptic occupancy of the competing axons nor axon diameter influenced myelination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CST myelination likewise occurs in the postnatal period in domestic pigs, reaching a mature state by 6 postnatal months ( Fang et al, 2005 ). Because completion of neural circuit formation and myelination of axonal branches are interrelated events ( Wang et al, 2021 ), no major changes are expected in the healthy cortical motor system connectivity after the first half-year of postnatal life in domestic pigs, except for changes in the number of axonal endings, synaptic maturation, and physiological remodeling associated to learning and neural activity ( Martin, 2005 ). In this regard, development of corticomotoneuronal connections deserves consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Triangularis sterni explants were isolated as previously described ( Kerschensteiner et al, 2008 ; Wang et al, 2021 ) from mice expressing a SEP-Nfasc186 transgene on either a WT, Nfasc -/- , or Cntnap1 -/- background. Following dissection of the thorax, the nerve muscle explant was pinned using minutin pins (Fine Science Tools) in a 40 mm inner well of a 60 mm Sylgard 184-coated dish containing oxygenated (95% O 2 , 5% CO 2 ) and cooled Ringers solution (125 mM NaCl, 2.5 mM KCl, 2 mM CaCl 2 , 1 mM MgCl 2 , 1.25 NaH 2 PO 4 , 26 mM NaHCO 3 , 20 mM glucose).…”
Section: Methodsmentioning
confidence: 99%